Pre‐exposure prophylaxis use in blood donors in England - Debrah, Jaid; Reynolds, Claire; Maddox, Victoria; Secret, Shannah; Baklan, Hatice; Amara, Alieu; Else, Laura; Simmonds, Peter; Brailsford, Susan R.; Khoo, Saye; Harvala, Heli (Wiley, 2026)
Background and Objectives
The For the Assessment of Individualized Risk (FAIR) framework, introduced by NHS Blood and Transplant (NHSBT) in 2021, aims to reduce stigma and improve equity in blood donor selection, particularly for gay, bisexual and other men who have sex with men (GBMSM). While pre-exposure prophylaxis (PrEP) is highly effective at preventing sexual transmission of human immunodeficiency virus, its declared use excludes individuals from blood donation. This study examined PrEP use among male blood donors with current or past syphilis in England to evaluate guideline compliance and implications for blood safety.
Materials and Methods
Residual plasma samples from syphilis-positive male blood donors collected in 2023 were tested for PrEP. These data were combined with two previous studies of syphilis-positive donors conducted between July 2018 and June 2024, incorporating demographics and reported PrEP use.
Results
The rate of syphilis-positive blood donations increased from 4.09 to 10.32 per 100,000 donations between 2018 and 2024 (p = 0.048, Mann–Kendall trend test) with a rising proportion of past syphilis cases attributed to GBMSM (18%–37%; p = 0.004, Fisher's test, p = 0.001 Mann–Kendall test); 7.1% of syphilis-positive blood samples from male blood donors tested positive for PrEP in 2023, indicating frequent non-compliance with donation guidelines.
Conclusion
Persistent PrEP use among syphilis-positive donors since 2018 suggests gaps in donor education regarding eligibility. Targeted public health interventions, particularly for younger GBMSM, are needed to strengthen sexual health education, PrEP messaging and awareness of donation criteria. Further research into other infections associated with high-risk sexual behaviour is warranted.